An Evaluation of the Tahfiz Qur’an Program Using the Discrepancy Model - Vita Aulia Maryatun; Sony Zulfikasari (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2025)
This research aims to assess the Tahfiz Qur'an program at SMP Darul Fikr Andong. This research is a qualitative approach using the Discrepancy evaluation model. Qualitative data was gathered through a case study regarding the implementation of the Tahfiz Qur'an Program at SMP Darul Fikr Andong. This data collection involved in-depth interviews with the principal, program coordinator, Tahfiz teacher, and students, as well as observations and documentation. The data analysis technique used was the Miles and Huberman technique. The result shows that the Tahfiz Qur’an program at SMP Darul Fikr Andong is systematically designed to align with the school's vision and mission. Installation evaluation shows teachers have memorized 30 juz, but there are gaps in teacher recruitment, student-teacher ratio, and supporting facilities. The learning process is adaptive and innovative, but is significantly challenged in students' motivation and the classroom environment. The program positively impacts students' Qur’an reading skills, character, and intellectual growth, yet many have not met the memorization target. The program is considered cost-effective based on current resources and benefits delivered. The Tahfiz Qur’an program should be sustained through strategic improvements across three crucial dimensions: systematic recruitment of qualified Tahfiz teachers, upgrades to the provision of supporting facilities, and intervention to bolster students' motivation and engagement.